1990
DOI: 10.1007/bf00223488
|View full text |Cite
|
Sign up to set email alerts
|

Control of glycolysis in rat liver by glucokinase and phosphofructokinase: influence of glucose concentration

Abstract: Control of glucose metabolism in rat liver under different glucose concentrations was studied. Flux Control Coefficients of glucokinase, glucose 6-phosphate isomerase and phosphofructokinase were determined by the 'shortening and enzyme titration' method. Results obtained show that glucose concentration in liver can play an important role in control of liver glycolysis by enhancing the Flux Control Coefficient of phosphofructokinase. Possible physiological significance of this fact is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Similarly, among the top 30 fold change genes affected by fasting, 19 genes can be clustered in metabolic process. For example, Gck and Pklr among the 19 genes encoding hexokinase and pyruvate kinase respectively, are the key genes involved in glycolysis process [14], [31]. It has been reported that the flux through glycolysis process is attenuated in response to fasting [32].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, among the top 30 fold change genes affected by fasting, 19 genes can be clustered in metabolic process. For example, Gck and Pklr among the 19 genes encoding hexokinase and pyruvate kinase respectively, are the key genes involved in glycolysis process [14], [31]. It has been reported that the flux through glycolysis process is attenuated in response to fasting [32].…”
Section: Discussionmentioning
confidence: 99%
“…The flux control coefficients obtained were CHK = 0.77, CGPI = 0.0 and CPFK = 0.24. Subsequently, similar experiments have been performed to calculate the control coefficients for the transition times in the pathway [119] and to determine how the flux control coefficients varied with glucose concentration [120]. Titration of enzymes by specific inhibitors.…”
Section: Methodsmentioning
confidence: 99%
“…To plot the graph about flux and enzyme activity, flux values were normalized with respect to the value of basal flux (without adding any extra enzyme), and enzyme activity values were divided by their respective K m values as described before (27).…”
Section: Metabolic Flux Control Assaymentioning
confidence: 99%